Direct reference, cognitive significance and Fregean sense - Branquinho, J; Branquinho, João M. B. V. (1992)
﻿ This essay deals with certain problems in the theory of singular reference. The following question is taken as central: What role is to be assigned to nonempty and syntactically simple singular terms in fixing the semantic contents of utterances of declarative sentences in which they may occur? I focus on those aspects of the current dispute between Millian and neo-Fregean approaches to singular reference which are related to issues about the cognitive significance of language use; the following two issues are singled out as crucial: the issue about (alleged) potential differences in informativeness between sentences constructed out of co-referential singular terms; and the issue about (alleged) failures of substitutivity salva veritate of co-referential singular terms in propositional-attitude contexts. The general direction of my arguments is as follows. On the one hand, I argue that "notational variance" claims recently advanced on both sides of the dispute should be deemed unsound; and hence that one is really confronted with separate accounts of singular content. On the other, I argue that Milllanism does not provide us with a satisfactory solution to the problems about cognitive significance; and hence that a framework of singular senses is Indispensable to deal with such problems in an adequate way. I also discuss the problem of Cognitive Dynamics, i.e. the issue of attitude-retention and persistence of mental content, in connection with the individuation of indexical thought. I argue that the standard Intuitive Criterion of Difference for thoughts might be reasonably extended to the diachronic case, allowing thus the possibility of discriminating between thoughts entertained by a thinker at different times.